A new policy framework for Myanmar's SME development - Masato Abe; Madhurjya Kumar Dutta (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2014)
Myanmar's emergence from decades of isolation provides an opportunity to learn from the experiences of its neighbours to guide its economic transition and achieve strong and inclusive growth. The development of small and medium-sized enterprises (SMEs) is an effective mechanism in achieving socioeconomic growth, but Myanmar poses a list of challenges that need to be overcome first, including poor infrastructure and limited market access. This paper proposes policy recommendations under seven key issues: business enabling environment, entrepreneurship development, access to financing, business development services, innovation and technology, market access, and cluster development. These recommendations are based on existing reviews of the Myanmar business community and the SME policy frameworks of various countries and combine to form a comprehensive policy framework. This policy framework will provide the government of Myanmar an opportunity to facilitate SME development, and with that the development of the country.
Keywords: L53; O10; O25; 330; Small and medium-sized enterprises; economic development; Myanmar; clusters; innovation and technology; business development services